المعالجة الإعلامية لقضايا التنمية الاقتصادية في الصحف الالكترونية الجزائرية الخاصة - صالحي,حده; زياد,اسماعيل (University of Eloued جامعة الوادي, 2024)
تهدف هذه الدراسة إلى التعرف على الكيفية التي عالجت بها الصحافة الجزائرية الخاصة القضايا التنموية في القطاع الاقتصادي من خلال موقع الشروق أون لاين، عن طريق المنهج المسحي و أداة تحليل المحتوى كميا وكيفيا. وقد توصلت الدراسة الى عدة نتائج أهمها ان الموقع لا يعتمد على الجانب التفسيري والتحليلي بقدر اعتماده على الأنواع الصحفية الإخبارية، كما تبين أن الشروق أون لاين تحاول تدعيم المساعي الحكومية في المجال الاقتصادي وتطوير التنمية. Abstract: This study aims to identify how the Algerian private press addressed development issues in the economic sector through the Chorouk Online website, through the survey method and the quantitative and qualitative content analysis tool. The study reached several results, the most important of which is that the site does not rely on the interpretive and analytical aspect as much as it relies on the types of news journalism. It also showed that Al-Chorouk Online is trying to support government efforts in the economic field and development .
Keywords: المعالجة الإعلامية; الإعلام التنموي; الخطاب الإعلامي; الصحافة الإلكترونية; Media treatment; economic development; development media; media discourse; electronic journalism